A study on relationship of facebook and game addictive behaviour with personality traits among medical students - Saini, Vijay Kumar; Baniya, Girish Chandra; Verma, K. K.; Soni, Aditya; Kesharwani, Santosh Kumar (International Journal of Research in Medical Sciences, 2017)
Background: Use of social networking sites and playing internet games are more common web activities among adolescents. Students are more prone to internet abuse for several reasons- natural affinity towards internet, free and unlimited access, flexible schedules, and freedom from parental interference and psychological immaturity. The aim was to study on relationship of facebook and game addictive behaviour with personality characteristics among medical students. Methods: This was a cross sectional observational study, carried out on 140 medical students. All the students were taken randomly. Assessment of sociodemographic details was done with the help of semi-structured performa, bergen facebook addiction scale, game addiction scale and big five inventory were used to see facebook and game addictive behavior and personality traits. Statistical analysis used for comparison of dichotomous variables chi-square test. Correlation and Linear regression was applied to see association. Data analysis was done with the help of statistical software SPSS 23. 0. Results: Mean score of facebook addiction scale among medical students was 39.94 (S.D. 13.133) and mean score of Game addiction scale was 11.19 (S.D. 04.966). It was found that agreeableness (β= -0.275, p=0.000) and extraversion (β = -0.368, p = 0.000) displayed significant associations with FB Total. While neuroticism (β=0.277, p=0.001) and agreeableness (β= -0.177, p=0.029) displayed significant associations with game addictive behavior. Conclusions: In our study we conclude that students with high agreeableness, high neuroticism and low extraversion were more related with Facebook and game addictive behavior. Extraversion was the most powerful predictor of Facebook addiction and neuroticism for gaming addiction.